2008
DOI: 10.1159/000161865
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Fitness, Insulin Resistance and Metabolic Syndrome in Severely Obese Prepubertal Italian Children

Abstract: Aim: To evaluate if insulin resistance (IR) and metabolic syndrome (MS) were associated with poor cardiovascular fitness in very obese prepubertal Italian subjects. Methods: Children referred to the Endocrinology and Diabetes Unit of Bambino Gesù Children’s Hospital underwent an OGTT with glucose and insulin assays. QUICKI, ISI and HOMA-IR were calculated. Total and HDL cholesterol, triglycerides and percentage of body fat (DEXA) were determined. Cardiovascular fitness (maximal treadmill time) was evaluated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 75 publications
1
16
0
Order By: Relevance
“…The difference in perceived exertion, especially in children/adolescents, has already been demonstrated in other studies . Our data, in accordance with other studies , suggest that a physically active lifestyle has beneficial effects on glucose homeostasis and insulin sensitivity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The difference in perceived exertion, especially in children/adolescents, has already been demonstrated in other studies . Our data, in accordance with other studies , suggest that a physically active lifestyle has beneficial effects on glucose homeostasis and insulin sensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…Very recently, NAFLD has been proposed as a component of the MetS and seems to lead to a premature atherosclerosis . It has been shown that young obese patients, with or without NAFLD, display a reduced capacity to perform physical exercise .…”
Section: Discussionmentioning
confidence: 99%
“…When comparing changes in metabolic parameters between the three groups with stable or reduced BMI z-score and the group with increased BMI z-score adjustment was made for improvement in aerobic fitness where the data was available, since cardiovascular fitness and CVD risk factors might be independently related in obese children [49]. A previously published study found that low cardiovascular fitness was strongly associated with the clustering of CVD risk factors in children independent of country, age and sex [50].…”
Section: Discussionmentioning
confidence: 99%
“…Only 102 subjects (44%) had data on aerobic fitness, and when repeating the analyzes in the 102 subject only adjusting for gender, baseline BMI z-score and waist circumference we got the same results as when aerobic fitness were included in the model. Former research has demonstrated divergent results regarding the relationship between insulin resistance and physical fitness in obese children and adolescents, and the effect of fitness on insulin may be mediated through a direct pathway and indirectly through changes in body composition [49,51]. A newly published study among 6 th grade youths concluded that both fatness and fitness are associated with cardiometabolic risk factors, but that fatness has a stronger association than fitness [52].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that a total of ten studies adjusted for both fat and lean masses in their analyses [9,18,48,56,61,72,82,[93][94][95], with eight out of the ten studies still finding at least one independent association of SI with PA, CRF or strength, suggesting that additional pathways may exist independent of the amount of lean mass as well as fat mass.…”
Section: Controlling For Lean Mass As Well As Fatmentioning
confidence: 99%